2016
DOI: 10.1007/s12571-016-0579-5
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainable smallholder poultry interventions to promote food security and social, agricultural, and ecological resilience in the Luangwa Valley, Zambia

Abstract: In Zambia's Luangwa Valley, highly variable rainfall and lack of education, agricultural inputs, and market access constrain agricultural productivity, trapping smallholder farmers in chronic poverty and food insecurity. Human and animal disease (e.g. HIV and Newcastle Disease, respectively), further threaten the resilience of poor families. To cope with various shocks and stressors, many farmers employ short-term coping strategies that threaten ecosystem resilience. Community Markets for Conservation (COMACO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…Cost was the primary limitation to routine egg consumption in rural Zambia (Hong, Martey, Dumas, & Travis, ). Prior to an intervention that increased flock size and eggs production, households in rural Zambia sold eggs or chickens rather than for consumption (Dumas et al, ). A recent analysis showed that eggs are a very expensive source of calories in low‐income countries with caloric prices of these foods very strongly associated with consumption patterns among young children (Headey & Hirvonen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Cost was the primary limitation to routine egg consumption in rural Zambia (Hong, Martey, Dumas, & Travis, ). Prior to an intervention that increased flock size and eggs production, households in rural Zambia sold eggs or chickens rather than for consumption (Dumas et al, ). A recent analysis showed that eggs are a very expensive source of calories in low‐income countries with caloric prices of these foods very strongly associated with consumption patterns among young children (Headey & Hirvonen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Third—perhaps most importantly—as a means of offsetting high flock mortality, smallholders have repeatedly demonstrated a preference for allowing eggs from village chickens to hatch rather than consuming them at home (de Bruyn et al, ; Dumas et al, ; Dumas et al, ; Gueye, ; Olney et al, ). The multipurpose utility of poultry (as a source of food, income, and resilience in the face of shocks) requires a daily cost–benefit analysis on the part of the smallholder, who must weight the many demands of their household in the face of limited resources (Pell & Kristjanson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The design of the EPC was adapted from a previous, smaller pilot project in the area (Dumas et al, ). Each of the EPCs was stocked with 40 layer hens—considered to be a manageable number of hens for first‐time egg producers, that would fit within a reasonably small facility, and yet would produce a reasonable number of eggs for the local markets—and egg production began in September 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markets also serve as a common source of ND infection, sometimes through the random sale of infected birds during outbreaks to salvage those not yet showing clinical signs (Ahlers et al, ). Models for the sustainable control of ND under resource‐limiting conditions through the training of community vaccinators who work on a fee‐for‐service basis have proved sustainable in Sub‐Saharan Africa since the early 2000s (Alders et al, ; Alders, Bagnol, & Young, ; Alexander et al, ; Dumas et al, ; Table ). Vaccination of family poultry has received little attention from animal health services in Sub‐Saharan Africa with most funding from national governments and donors continuing to focus on ruminants.…”
Section: Disease Prevention and Controlmentioning
confidence: 99%